The Protective Effects of Ivabradine in Preventing Progression from Viral Myocarditis to Dilated Cardiomyopathy - Yue-Chun, Li; Guang-Yi, Chen; Li-Sha, Ge; Chao, Xing; Xinqiao, Tian; Cong, Lin; Xiao-Ya, Dai; Xiangjun, Yang (Frontiers in Pharmacology, 2016)
To study the beneficial effects of ivabradine in dilated cardiomyopathy (DCM) mice, which evolved from coxsackievirus B3-induced chronic viral myocarditis. Four-to-five-week-old male balb/c mice were inoculated intraperitoneally with coxsackievirus B3 (Strain Nancy) on days 1, 14, and 28. The day of the first virus inoculation was defined as day 1. Thirty-five days later, the surviving chronic viral myocarditis mice were divided randomly into two groups, a treatment group and an untreated group. Ivabradine was administered by gavage for 30 consecutive days in the treatment group, and the untreated group was administered normal saline. Masson’s trichrome stain was used to evaluate the fibrosis degree in myocardial tissue. The expression levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), collagen I, collagen III and p38-MAPK signaling pathway proteins were detected by Western blot. Electrocardiogram was used to investigate the heart rate and rhythm. The thickness of the ventricular septum and left ventricular posterior wall, left ventricular end diastolic dimension, left ventricular end systolic dimension, left ventricular ejection fractions and fractional shortening were studied by echocardiography. Compared with the untreated chronic viral myocarditis mice, ivabradine significantly increased the survival rate, attenuated the myocardial lesions and fibrosis, improved the impairment of the left ventricular function, diminished the heart dimension, decreased the production of collagen I and collagen III, reduced the expression of the proinflammatory cytokines TNF-α, IL-1β, and IL-6, and lowered the production of phospho-p38 MAPK. The findings indicate the therapeutic effect of ivabradine in preventing the progression from viral myocarditis to DCM in mice with chronic viral myocarditis induced by coxsackievirus B3, is associated with inhibition of the p38 MAPK pathway, downregulated inflammatory responses and decreased collagen expression. Ivabradine appears a promising approach for the treatment of patients with viral myocarditis.